Issues and Challenges in Developing Shariah Governance and Shariah Audit in Islamic Cooperatives - Nur Amni Mahmud Sabri; Supiah Salleh; Muhammad Iqmal Hisham Kamaruddin; Zurina Shafii; Mustafa Mohd Hanefah; Nurazalia Zakaria (Faculty of Syariah and Law (FSU), Selangor International Islamic University College (KUIS), 2024)
Volume: 6 No: 2 (Page: 01-18)